2019
DOI: 10.1002/1873-3468.13443
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the mesodermal transcriptional network by genome‐wide identification of Zinc finger homeodomain 1 (Zfh1) targets

Abstract: The Drosophila transcription factor (TF) Zfh1 has distinct roles compared to the cell lineage‐determining TFs in almost all mesoderm‐derived tissues. Here, we link Zfh1 to the well‐characterized mesodermal transcriptional network. We identify five enhancers integrating upstream regulatory inputs from mesodermal TFs and directing zfh1 expression in mesoderm. Most downstream Zfh1‐target genes are co‐bound by mesodermal TFs, suggesting that Zfh1 and mesodermal TFs act on the same sets of co‐regulated genes during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Using the available ChIP data relating to these four TFs (i.e. Zfh1, Bin, Mef2 and Doc2; Jakobsen et al, 2007 ; Zinzen et al, 2009 ; Junion et al, 2012 ; Wu et al, 2019 ), we scanned for their co-occupancy to DNA sequences flanking 16 genes that had previously been confirmed to be expressed in actively migrating CVM cells during stages 10-13 ( Bae et al, 2017 ). Enhancers regulating HLH54F and Doc2 had been identified previously ( Ismat et al, 2010 ; Kadam et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the available ChIP data relating to these four TFs (i.e. Zfh1, Bin, Mef2 and Doc2; Jakobsen et al, 2007 ; Zinzen et al, 2009 ; Junion et al, 2012 ; Wu et al, 2019 ), we scanned for their co-occupancy to DNA sequences flanking 16 genes that had previously been confirmed to be expressed in actively migrating CVM cells during stages 10-13 ( Bae et al, 2017 ). Enhancers regulating HLH54F and Doc2 had been identified previously ( Ismat et al, 2010 ; Kadam et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Predictions for CVM-specific enhancer elements were generated using 6-8 h ChIP-ChIP data for Zfh1 ( Wu et al, 2019 ), Bin ( Zinzen et al, 2009 ), Mef2 ( Zinzen et al, 2009 ) and Doc2 ( Junion et al, 2012 ). Priority was given to regions that showed occupancy by both Bin and Mef2 while excluding Twi ( Zinzen et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, ZEB1 represses transcription of epithelial determinants such as E-cadherin and Crumbs3 (Caramel et al, 2018). Similarly, in Drosophila, it has been shown by DamID-seq and ChIP-seq analyses that the E-cadherin gene shotgun (shg) is a direct target of Zfh1 (Albert et al, 2018;Wu et al, 2019). We found that expression of shg, which was detected by the shg-lacZ reporter (Genevet et al, 2009), was significantly downregulated by overexpression of Zfh1 (Figure 3M, compare with Figure 3L, quantified in Figure 3N).…”
Section: Notch Signaling Causes Invasion Of Src Cells Via Zfh1mediate...mentioning
confidence: 98%
“…Notably, Zfh1 blocks cell death of Src-activated cells by repressing hid. Zfh1 also prevents cell death by repressing rpr (Ohayon et al, 2009;Wu et al, 2019). Given that hid and rpr drive apoptosis of ''loser cells'' in cell competition (Nagata and Igaki, 2018), Zfh1 may also contribute to tumor progression via regulation of cell competition.…”
Section: Notch Signaling In Src Cells Drives Invasion Of Neighboring ...mentioning
confidence: 99%
“…ZEB is well known for triggering epithelial-to-mesenchymal transitions (EMT) in both developing embryos and cancer cells [74][75][76]. Zfh1 is also known to regulate mesoderm patterning in the embryo and adult intestinal stem cells [77,78]. Zfh1 is expressed in all AMPs during embryonic/larval development (Figure 1) [67] and persists in the adult MuSCs, where it is required to prevent differentiation and maintain stemness (Figure 2A) [16,17].…”
Section: Zfh1/zeb Maintains Undifferentiated Muscs: An Evolutionarily Conserved Functionmentioning
confidence: 99%